2014
DOI: 10.1002/mmce.20857
|View full text |Cite
|
Sign up to set email alerts
|

A new hybridized backtracking search optimization algorithm with differential evolution for sidelobe suppression of uniformly excited concentric circular antenna arrays

Abstract: In this work, a hybridized combination of backtracking search algorithm (BSA) with differential evolution (DE) is proposed and applied on sidelobe suppression problem of uniformly excited concentric circular antenna arrays (CCAA). Each array is assumed to have isotropic elements and be placed on x-y plane and has one center element. A search for optimal setting of ring radius and number of elements in each ring is carried out so as to achieve low sidelobe performance on overall azimuth plane. Care has been tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Exploitation and exploration are key search mechanisms in solving complex optimisation problems. Numerous optimisation cases have demonstrated that basic BSA has a strong ability of exploration because of its mutation and crossover strategies, which the better or worse individuals have the same probability to be selected. However, the poor exploitation of basic BSA is also because of the strategies, leading to the problems of slow convergence speed and low search precision.…”
Section: Enhancements Of Backtracking Search Optimisationmentioning
confidence: 99%
“…Exploitation and exploration are key search mechanisms in solving complex optimisation problems. Numerous optimisation cases have demonstrated that basic BSA has a strong ability of exploration because of its mutation and crossover strategies, which the better or worse individuals have the same probability to be selected. However, the poor exploitation of basic BSA is also because of the strategies, leading to the problems of slow convergence speed and low search precision.…”
Section: Enhancements Of Backtracking Search Optimisationmentioning
confidence: 99%
“…As a result, many improvement research studies have been developed to overcome the drawback. e major modified research studies include the following five categories: (1) modified BSA algorithms by developing hybridization mechanisms [31][32][33][34][35][36][37][38][39], (2) modified BSA algorithms by developing novel initialization mechanisms [40][41][42][43][44][45][46], (3) modified BSA algorithms by developing novel reproduction (mutation or crossover) mechanisms [47][48][49][50][51][52][53][54][55], (4) modified BSA algorithms by developing novel selection mechanisms [56][57][58][59][60], and (5) modified BSA algorithms by developing novel control mechanisms for parameters (including the control factor F which is randomly generated in the original BSA) [61][62][63][64][65][66][67][68][69].…”
Section: Introductionmentioning
confidence: 99%
“…One of the methods for side lobe suppression and beam control is to use optimization techniques. For antenna array applications, popular optimization techniques are genetic algorithm, ant colony optimization, simulated annealing, particle swarm optimization [10][11][12][13][14][15][16]. Differential equation with back tracking search algorithm is applied to reduce side lobe level of concentric circular array [10].…”
mentioning
confidence: 99%